Education And Training On Searching For Teaching Materials From The Internet For Teachers In Pangkep District - Edy Sabara; Retyana Wahrini; Mustamin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This Community Service Program (PkM) is entitled Education and Training on Searching Teaching Materials from the Internet for Teachers in Pangkep Regency. In the midst of globalization, teachers should not be like frogs in a shell. Teachers must have broad and globalized insights as an effort to improve education. Teachers should not only transfer information/learning materials that are